STRENGTHENING HISTORY EDUCATION IN BUILDING GENERATION Z'S NATIONALISM: A HUMANITIES AND DIGITAL LEARNING PERSPECTIVE: Penguatan Pendidikan Sejarah dalam Membangun Nasionalisme Generasi Z: Perspektif Humaniora dan Digital Learning - Naitboho, Yufitris; Kirana, Ave Regina Chandra; Da Silva, Nining Lestari; Sensi, Nataliana; Mas'ud, Fadil (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the role of humanities-based history education and the effectiveness of digital learning in fostering nationalism and historical awareness among Generation Z in the digital age. The background of this study is based on the need to transform history learning to make it more relevant, interactive, and meaningful for digital natives. The research method used a comparative literature study of various scientific articles, research reports, and empirical studies related to humanistic history learning and digital technology. The analysis was conducted by examining the main findings regarding the humanities perspective, digital learning design, and the relationship between the two in shaping national identity. The results show that the integration of the humanities and digital learning has been proven to increase historical empathy, critical thinking skills, and student engagement through immersive and contextual learning experiences. Furthermore, this approach strengthens Generation Z's nationalism in a reflective, inclusive, and value-based manner, as long as it is supported by competent teachers, ethical content curation, and equitable access to technology.